The Effect of Carrot (Daucus carota) Substitution on Sensory Characteristics of Fruit Leather Janten Banana (Musa eumusa) - Novita Herdiana; Susilawati Susilawati; Fibra Nurainy; Tyasto Prima Ahmadi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2023)
Fruit leather is a food product created by mashing and dehydrating fruit flesh into uniform thin sheets with unique texture and fruity flavor. This study aimed to optimize the production of high-quality fruit leather formulated with banana and carrot. The experimental design used in this study was a Complete Randomized Block Design (CRBD) with a single factor and 4 replications. Six levels of banana and carrot ratio was used in this research which were (P1) 100:0, (P2) 90:10, (P3) 80:20, (P4) 70:30, (P5) 60:40, and (P6) 50:50. Subsequently, a scoring test was conducted by 15 semi-trained individuals, followed by a hedonic test by 25 untrained panelists. To evaluate data consistency, Bartlett's test and Tuckey's test were applied, and thereafter, variance analysis was conducted to determine the effect between treatments. In cases where a significant effect was observed, further analysis was conducted utilizing the Least Significant Difference Test (LSDT) at a significant level of 5%. The results showed that the carrot concentration affected the overall sensory reception, color, and taste of the fruit leather. The most favorable outcomes were linked to the treatment involving 50% carrot substitution (P6), characterized by color, texture, aroma, taste, and overall acceptance ratings of 3.90 (brownish orange – orange), 3.30 (slightly plastic – plastic), 2.98 (dislike – neutral), 3.59 (neutral – like), and 3.77 (neutral – like), respectively.